Actionability and Simulation: No Representation without Communication - Feldman, Jerome A. (Frontiers in Psychology, 2016)
.There remains considerable controversy about how the brain operates. This review focuses on brain activity rather than just structure and on concepts of action and actionability rather than truth conditions. Neural Communication is reviewed as a crucial aspect of neural encoding. Consequently, logical inference is superseded by neural simulation. Some remaining mysteries are discussed.